Dipping Impact on the Bond Strength between Zirconia Ceramic and a Resin Cement - Berjani, Naeem; Mahshid, Minoo; Tabatabaian, Farhad; Sadr, Seyed Jalil (Regeneration, Reconstruction & Restoration (Triple R), 2017)
Introduction: Dipping technique is commonly used by dental technicians to color zirconia ceramics; however, its impact on the bond between zirconia and resin cements is unclear. This in vitro study aimed to evaluate the microtensile bond strength (µTBS) between a zirconia ceramic and Panavia F2.0 resin cement after dipping in coloring liquids with different shades. Materials and Methods: Twenty zirconia blocks were dipped in four different shades of coloring liquids including A3, B2, C1, and D4, while five blocks were not colored for the control. All zirconia blocks were cemented to corresponding composite blocks using Panavia F2.0 resin cement. Zirconia-cement-composite blocks were cut into one hundred microbar specimens (1×1×10 mm). The specimens were divided into five studied groups according to their shade (A3, B2, C1, D4, control) and were subjected to an aging process. A microtensile tester applied tensile forces to the specimens, till the fracture occurred, and measured the µTBS values. One-way ANOVA and Tukey’s Post Hoc were used to analyze the data (P<0.05). Optical microscopy and scanning electron microscopy were employed to evaluate failure modes and surface structure. Results: The µTBS values for the groups showed significant differences (P<0.0001). D4 had the highest, and B2 had the lowest µTBS values. C1 (P=0.69) and A3 (P=0.89) showed no significant differences in the µTBS values compared with the control. Failure modes evaluation represented the lowest rate of adhesive failure for D4 (10%), and the highest in this respect for B2 (80%). Conclusion: Depending on the shade of coloring liquids, dipping had positive, negative, or no effects on the µTBS of zirconia ceramic to Panavia F2.0 resin cement.